Response of thoracolumbar vertebral bodies to high rate compressive loading - biomed 2013 - Dooley, C J; Wester, B A; Wing, I D; Voo, L M; Armiger, R S; Merkle, A C (Biomedical sciences instrumentation, 2013)
Underbody blast (UBB) events created by improvised explosive devices are threats to warfighter survivability. High intensity blast waves emitted from these devices transfer large forces through vehicle structures to occupants, often resulting in injuries including debilitating spinal fractures. The vertical loading vector through the spine generates significant compressive forces at high strain rates. To better understand injury mechanisms and ultimately better protect vehicle occupants against UBB attacks, high-fidelity computational models are being developed to predict the human response to dynamic loading characteristic of these events. This effort details the results from a series of 23 high-rate compression tests on vertebral body specimen. A high-rate servo-hydraulic test system applied a range of compressive loading rates (.01 mm/s to 1238 mm/s) to vertebral bodies in the thoracolumbar region (T7-L5). The force-deflection curves generated indicate rate dependent sensitivity of vertebral stiffness, ultimate load and ultimate deflection. Specimen subjected to high-rate dynamic loading to failure experienced critical structural damage at 5.5% ± 2.1% deflection. Compared to quasi-static loading, vertebral bodies had greater stiffness, greater force to failure, and lower ultimate failure deflection at high rates. Post-failure, an average loss in height of 15% was observed, along with a mean reduction in strength of 48%. The resulting data from these tests will allow for enhanced biofidelity of computational models by characterizing the vertebral stiffness response and ultimate deflection at rates representative of UBB events.